1995
DOI: 10.1007/bf01076893
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between elevated lipid peroxides, vitamin E deficiency and hypertension in preeclampsia

Abstract: Preeclampsia or pregnancy-induced hypertension is a major cause of both maternal and fetal-neonatal morbidity and mortality. The deficiency of vitamin E can cause accumulation of lipid peroxidation products, which, in turn, can induce vasoconstriction. This study has examined any evidence of increased cellular lipid peroxidation and accumulation of malonydialdehyde (MDA, an end product of lipid peroxidation) in pregnancy-induced hypertension and any relationship between the elevated MDA and lower vitamin E lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 24 publications
2
21
5
Order By: Relevance
“…The vitamin E is a potent antioxidant that protects the cell membrane against enzyme activity, free radicals or highly reactive degradation products during pregnancy. 6,9,10,21,23 The results of the present study are in consistence with the previous studies. They suggested that significant rise in lipid peroxides with decreased vitamin E levels are possible causative factors for the pathogenesis Table II shows the comparison of serum MDA levels between groups and Table III shows the comparison of serum vitamin E levels between groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The vitamin E is a potent antioxidant that protects the cell membrane against enzyme activity, free radicals or highly reactive degradation products during pregnancy. 6,9,10,21,23 The results of the present study are in consistence with the previous studies. They suggested that significant rise in lipid peroxides with decreased vitamin E levels are possible causative factors for the pathogenesis Table II shows the comparison of serum MDA levels between groups and Table III shows the comparison of serum vitamin E levels between groups.…”
Section: Discussionsupporting
confidence: 92%
“…4,7,10.11 Several studies demonstrated that preeclampsia is associated with increased utilization of antioxidants. 8,10,19,21 In the present study, the plasma levels of vitamin E were significantly lower in preeclampsia and in normal pregnancy than that of healthy nonpregnant women. These findings are in agreement with the findings of other research workers.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Serum MDA levels were significantly increased in PIH, preeclampsia and eclampsia compared to normal third trimester pregnant women. Jain SK and Wise R 13 20 found that antioxidant activity was markedly reduced in preeclampsia. The excessive generation of free radicals inactivates the enzymes system in the body leading to decreased SOD activity observed in present study.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been assumed that reduced placental perfusion generates free radicals generating systemic oxidative damage, as supported by evidence of OS in the circulation and tissues of women with pre-eclampsia (Roberts et al, 2003). Gratacó s et al (1998) and Jain and Wise (1995) confirmed that serum lipid peroxide levels are significantly higher and serum vitamin E levels significantly lower in women with pre-eclampsia than in women with normal pregnancies. In this regard, the reduction in maternal and placenta antioxidant defense in pre-eclampsia is linked to an excessive depletion of antioxidants through the increased generation of oxygen free radicals (Jauniaux et al, 2006).…”
Section: Placentationmentioning
confidence: 96%